Muscarinic receptor mediated cAMP response in human K562 chronic myelogenous leukemia cells - (:unkn) unknown (TURKISH BIOCHEM SOC, 2011)
Objectives: Muscarinic acetylcholine receptors play key roles in regulating many diverse physiological processes. Recent studies suggest that muscarinic receptors mediate some cellular events in hematopoietic cells. Muscarinic receptors are expressed in different human cells. cAMP an intracellular signaling molecule, is involved in a wide variety of physiological functions and stimulation of muscarinic receptors leads to the alteration of intracellular cAMP levels. The present study investigated muscarinic receptors mediated cAMP level in K562 chronic myelogenous leukemic cells. Methods: Muscarinic receptor mediated cAMP formation was measured by using the cAMP system colorimetric kit. Results: Carbachol stimulated intracellular cAMP accumulation in K562 chronic myelogenous leukemic cells. The stimulatory effect of carbachol was abolished by atropine and tropicamide, while gallamine had little effect. The calcium chelator 1,2- bis( o-aminophenoxy)ethane-N,N,N',N'-tetraacetic acid tetra( acetoxymethyl) ester inhibited effects of carbachol on the production of cAMP in K562 cells. Conclusions: These results suggest that muscarinic receptor activation is linked to adenylate cyclase stimulation in K562 chronic myelogenous leukemic cells.
Keywords: Adenylate cyclase; signal transduction; carbachol; CEREBELLAR GRANULE CELLS; INDUCED DOWN-REGULATION; ACETYLCHOLINE-RECEPTOR; ADENYLYL-CYCLASE; MESSENGER-RNA; CHOLINERGIC SYSTEM; PHOSPHOLIPASE-C; PERIPHERAL-TISSUES; EXPRESSION; SUBTYPES